Reduction of Nonconformity from Human Error in Assembly Process of Spindle Motor for Hard Disk Drive - Vasasiri, Vathasil; Ploypanichcharoen, Kitisak (Thai Industrial Engineering Network Journal, 2017)
This research quested for dent and/or scratch problem in spindle motor for a hard disk drive industry. It initiated the vital few of cost of poor quality in the sample company. The Alpha-1 at OD position, spindle motor’s model, in rotor assembly process was the scope of this study which can reflect the problem. The proportion, dent and/or scratch at OD position of total production input, was 710 ppm and management aimed at 280 ppm. Principal Component Analysis founded the first component contributed for 75.6% of total variation. The subjective interpretation of contributor was human error. To achieve the target, problem must be reduced 60.8% of total problem which mathematically implied 80.4% of total human error. The research journey started at measurement system evaluation and analysis which founded those effectiveness indices of measurement system, dent and scratch at OD position, were unacceptable in both of miss alarm (IMISS) indices and false alarm (IFA) indices. To eliminate the causes from measurement, method of inspection was improved and operators were retrained after improvement. In RCA part, human error was analyzed by system approach. It generated the hypothesizes which were physical fatigue of operators, circadian rhythm of operators, work environment between morning shift and night shift, lack of an accountability system, the difference method between machines and the difference skill of operators from team rotation. The 2-Proportion test was implemented to prove the causes from human error. The study founded that the difference skill of operators from team rotation and lack of an accountability system was significant for improvement. The P-Values of the average proportion of dent and/or scratch at OD position were 0.0001 and 0.0019 respectively. In order to counter the causes, operation was redesigned to reduce skill-related work and process of accountability was fulfilled in operation. The result of these countermeasures shall reduce the operation which relies on operators’ skill and shall increase human awareness. The average proportion of dent and/or scratch, OD position, shall approximately achieve the target at 276 ppm.